Analisis Pola Komunikasi Tim Sosmed Kreatif Prodi Ilkom Universitas Pasundan Pada Aplikasi Trello - Assyifa Uzzahro Khoerunnisa; Suparman Suparman; Amiruddin Saleh; Rici Tri Harpin Pranata; Nabila Manisya; Khalila Zahra Maharani; Maharani Azzahra; Anggia Widia Khairunnisa (CV. ULIL ALBAB CORP, 2025)
Technological advances gave birth to digital platforms that have influenced the way groups communicate to produce higher efficiency in performing daily tasks, one of which is the presence of Trello as a project management application. This study aims to determine the communication patterns of the creative social media team of the Ilkom study program at Pasundan University on the Trello application. This research method is qualitative with a constructivism paradigm using data collection methods through in-depth interviews. This study found that the communication pattern used was a star or comprehensive communication pattern (All channel). It was also found that the benefits of using Trello on the team are streamlining work time, reducing miscommunication from convoluted and non-transparent coordination processes, making work more structured and increasing the discipline of team members in completing work and communicating. This study illustrates that utilizing the Trello application can support better team communication to make it easier to manage work.